The pastoral care of preaching and the trauma of HIV and AIDS - Streets, F. J. (Verbum et Ecclesia, 2008)
There is within the history of Christian worship practices a long tradition of someone offering a sermon to those gathered for worship. The primary means for many Christians throughout the world of receiving Christian education and guidance is by listening to sermons. There is generally embedded in all Christian preaching some attempt on the part of the preacher to share a worldview based upon the his or her biblical and theological interpretation of the meaning of faith and their application to daily living. This article explores how the sermon can be a source of religious instruction and aspect of pastoral caring for those infected and affected by HIV and AIDS. The article also suggests that such sermons can be a form of advocating social justice for those who are stigmatized because of their HIV status. Note: The people mentioned in this article, are real but, their names, Rob, Inspiration and Pastor Able are fictitious for reasons of confidentiality. "My Africa is fading and no one sees or cares that it is happening."
Free